2014
DOI: 10.1063/1.4897008
|View full text |Cite
|
Sign up to set email alerts
|

Gate assisted Kelvin test structure to measure the electron and hole flows at the same nanowire contacts

Abstract: A gate assisted Kelvin test structure based on Si nanowire field effect transistors has been designed and fabricated for the characterization of the transistor source/drain contacts. Because the Si nanowire field effect transistors exhibit ambipolar characteristics with electron current slightly lower than the hole current, we can select the type of carriers (electrons or holes) flowing through the same contacts and adjust the current by the applied gate voltage. In this way, we are able to measure the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Our previous work has shown that using the gate-assisted test structures is an excellent approach to measure properties of the metal contacts to low-dimensional materials. 31 Here, we present a study on current crowding in metal-MoS 2 contacts determined by using both gate-assisted Kelvin structures and four-probe structures where the channel current is effectively tuned by a top gate.…”
mentioning
confidence: 99%
“…Our previous work has shown that using the gate-assisted test structures is an excellent approach to measure properties of the metal contacts to low-dimensional materials. 31 Here, we present a study on current crowding in metal-MoS 2 contacts determined by using both gate-assisted Kelvin structures and four-probe structures where the channel current is effectively tuned by a top gate.…”
mentioning
confidence: 99%